Comparative evaluation of midazolam and butorphanol as oral premedication in pediatric patients - Chandni Sinha; Manpreet Kaur; Ajeet Kumar; Anand Kulkarni; M Ambareesha; Madhusudan Upadya (Wolters Kluwer Medknow Publications, 2012)
Background: To compare oral midazolam (0.5 mg/kg) with oral butorphanol (0.2 mg/kg) as a premedication in 60 pediatric patients with regards to sedation, anxiolysis, rescue analgesic requirement, and recovery profile. Materials and Methods: In a double blinded study design, 60 pediatric patients belonging to ASA class I and II between the age group of 2-12 years scheduled for elective surgery were randomized to receive either oral midazolam (group I) or oral butorphanol (group II) 30 min before induction of anesthesia. The children were evaluated for levels of sedation and anxiety at the time of separation from the parents, venepuncture, and at the time of facemask application for induction of anesthesia. Rescue analgesic requirement, postoperative recovery, and complications were also recorded. Results: Butorphanol had better sedation potential than oral midazolam with comparable anxiolysis at the time of separation of children from their parents. Midazolam proved to be a better anxiolytic during venepuncture and facemask application. Butorphanol reduced need for supplemental analgesics perioperatively without an increase in side effects such as nausea, vomiting, or unpleasant postoperative recovery. Conclusion: Oral butorphanol is a better premedication than midazolam in children in view of its excellent sedative and analgesic properties. It does not increase side effects significantly.